Prevalence and socio-demographic correlates of multi-modal cannabis use among young adults who currently use cannabis - Caroline North; Srishty Arora; C. Nathan Marti; Jacob E. Thomas; Keryn E. Pasch; Anna V. Wilkinson; Alexandra Loukas (Preventive Medicine Reports, 2024)
Cannabis use is common in young adulthood, yet little is known about the prevalence and patterns of multi-modal (i.e., use of more than one mode) cannabis use. Objective: We aimed to (1) determine the past 30-day prevalence of five modes (smoke, vape, edible, dab, other) of cannabis use, (2) describe the prevalence of multi-modal cannabis use (single vs. dual vs. poly-modal), and (3) identify socio-demographic correlates of multi-modal use among young adults. Method: Participants were 764 22–30-year-olds who currently used cannabis from Wave 9 (Spring 2019) of the Marketing and Promotions Across Colleges in Texas Project. Participants were 25.11 years old on average (SD = 1.81), 63.6% female, 38.7% identified as non-Hispanic white, 30.6% as Hispanic/Latino, 13.0% as Asian and 9.4% as Black, and 8.2% identified with two or more races or another race/ethnicity. Bivariate analyses and a multinomial regression were used to examine study questions. Results: Smoking was the most common mode of cannabis use followed by vaping and then edibles. Nearly 43% of participants reported single-modal cannabis use, 33% reported dual-modal use, and 24% reported poly-modal use. Males and those identifying as non-heterosexual were at a greater risk than their counterparts for using multiple modes of cannabis. Participants identifying as Black were at a reduced risk for poly-modal compared to single-modal use. Conclusion: Multi-modal use is common among young adults who currently use cannabis, indicating a need for universal efforts aimed at all young adults. Tailored interventions aimed toward those at elevated risk for multi-modal use also are needed.